2010
DOI: 10.1111/j.1471-0528.2010.02775.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of progress of labour using intrapartum translabial ultrasound, assessing head station, direction, and angle of descent

Abstract: Objective Intrapartum translabial ultrasound (ITU) has the potential to objectively and quantitatively assess the progress of labour. The relationships between the different ITU parameters and their development during normal term labour have not been studied.Design Observational study.Setting University teaching hospital.Population Labouring women with normal term fetuses in cephalic presentation.Methods Intrapartum translabial ultrasound measurements for 'head station', 'head direction', and 'angle of descent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
177
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 21 publications
13
177
0
2
Order By: Relevance
“…The value of this conversion was recently appreciated in another article in UOG 4 . The angle of descent is also easy to obtain and is reproducible 3,5 . We suggest using the parameter 'head direction' -in addition to head station -as we initially described it, because it enables a simple assessment 'at a glance'.…”
Section: Quantification Of Fetal Head Direction and Descentmentioning
confidence: 99%
See 3 more Smart Citations
“…The value of this conversion was recently appreciated in another article in UOG 4 . The angle of descent is also easy to obtain and is reproducible 3,5 . We suggest using the parameter 'head direction' -in addition to head station -as we initially described it, because it enables a simple assessment 'at a glance'.…”
Section: Quantification Of Fetal Head Direction and Descentmentioning
confidence: 99%
“…In a recent study 3 , we showed that head direction and the dynamics of head descent during a contraction and over the course of delivery depend on the absolute head station: at higher stations, head direction tends to be 'horizontal' or even 'down', but at ITU-measured head stations of 0 to +2, a marked upward change in direction occurs during a contraction (see videos S1 and S2 in Tutschek et al 3 ). Head station is measured as shown in Figure 1.…”
Section: Quantification Of Fetal Head Direction and Descentmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Further understanding of the complex physiology of childbirth is possible due to intrapartum ultrasonography. It has been shown to provide objective information on the dynamics of different stages of labor.…”
Section: Intrapartum Ultrasonography For Prediction Of Vaginal Delivementioning
confidence: 99%